Workshop on eco-enzyme production as the implementation of zero waste concept at SD Muhammadiyah PK Kottabarat Surakarta - Lina Agustina; Rina Astuti; Aminah Asngad; Suparti Suparti; Erma Musbita Tyastuti; Siti Kartika Sari (Community Empowerment, 2024)
68% of household waste consists of organic waste, which significantly contributes to environmental pollution and can cause disruption if not managed properly. Unfortunately, proper management of organic waste is lacking, with a predominant method of disposal being dumping in empty land, waterways, or burning. However, organic waste holds potential for eco-friendly solutions such as eco enzymes. The objective of this community service initiative was to train individuals in producing eco enzymes from organic waste at SD Muhammadiyah PK Kottabarat Surakarta. The activities included educating the community about organic waste processing and conducting training sessions on eco enzyme production, including packaging and labeling. As a result of these efforts, teachers and students at SD Muhammadiyah Kottabarat gained the skills to utilize leftover fruit and vegetable waste, producing a total of 18 liters of eco enzymes. This included 2 jars of eco enzymes from vegetable waste and 4 jars from orange peels.